METODE PEMAHAMAN HADIS - Muhammad Asriady (EKSPOSE, 2017)
understanding of hadith method is the way to understand the hadith. The book entitled Methodology of Understanding Hadiths written by Arifuddin Ahmad was developed into several techniques, such as textual interpretation techniques, contextual interpretations, and intertextual interpretations. In this study, the writer used library research methodology. The development of hadith from time to time is very fast, so in understanding the hadith there were various methods. Researchers and observers must understand the methodology so that the diverse views on Islam can be understood in depth, it can bringing the people to the Rahmatan Lil Alamin